Computational functions of neurons and circuits signaling injury: relationship to pain behavior - Mendell, Lorne M (Proceedings of the National Academy of Sciences - PNAS, 2011)
The basic circuitry of the "pain pathway" mediating transmission of information from the periphery to the brain is well known, consisting of specialized sensory fibers known as nociceptors projecting to specific spinal cord neurons, which in turn project on to the thalamus and cerebral cortex. Here we survey some of the unique properties of these circuits, such as peripheral and central sensitization, and the segmental and descending modulatory control of synaptic transmission. We also review evidence indicating dissociation between nociceptor activity and behavioral indications of pain. Together, these considerations point to the need for a more quantitative approach to the nociceptive system, specifically the interactions at peripheral, spinal, and supraspinal levels as well as between them, to more fully understand how the activity in nociceptive neurons individually and collectively is related to the pain response.